Social Entrepreneurship - Richez-Battesti, Nadine; Petrella, Francesca (Encyclopedia of Creativity, Invention, Innovation and Entrepreneurship, 2013)
Social entrepreneurship is commonly used to qualify all economic initiatives that serve social and/or environmental mission and that reinvest a large part of their surpluses in support of their mission. Although this definition is not yet stabilized and its boundaries remain unclear, it focuses on the aim to achieve both economic efficiency and social innovation. It takes place within a context of great uncertainty about the future of welfare states and their capacity to meet new societal needs, of financial and budgetary constraints that force public authorities to develop new forms of interaction between public and private sectors, and therefore, of need to build new responses to societal challenges that are sustainable socially, economically, and environmentally. Within this context, all sorts of initiatives that can be qualified as social innovations are gaining interest.
Keywords: Ouvrages de référence; Réservé UdeM

Social Entrepreneurship - Richez-Battesti, Nadine; Petrella, Francesca (Encyclopedia of Creativity, Invention, Innovation and Entrepreneurship, 2013)
Social entrepreneurship is commonly used to qualify all economic initiatives that serve social and/or environmental mission and that reinvest a large part of their surpluses in support of their mission. Although this definition is not yet stabilized and its boundaries remain unclear, it focuses on the aim to achieve both economic efficiency and social innovation. It takes place within a context of great uncertainty about the future of welfare states and their capacity to meet new societal needs, of financial and budgetary constraints that force public authorities to develop new forms of interaction between public and private sectors, and therefore, of need to build new responses to societal challenges that are sustainable socially, economically, and environmentally. Within this context, all sorts of initiatives that can be qualified as social innovations are gaining interest.
Keywords: Ouvrages de référence; Réservé UdeM